The concept and mechanisms of implementation of international humanitarian law (comparative study) - Ahmed, Abker Ali Abdul Majid; Abdel Rahim, Ahmed Hammad Abd Allah; Ahmed, Ahmed Douma Rahma (Journal of Economic, Administrative and Legal Sciences, 2017)
The international humanitarian law is mere a fruits for a set of ethics and moral values that call for peaceful solutions and rejecting wars between estates. This international law, aimed at restricting power using in armed conflicts for two reasons: The first one is reducing the violence effects that exceed the allowed limits on combatants, while the second is avoiding harming those who have no hand in conflicts. The topic has been discussed in three chapters, the first tackled the understanding of the international humanitarian law, acknowledging it, explaining its nature and its contents as basic settled principals in the Islamic sharia though not mentioned namely. We have produced from Arabic and Islamic history models telling the extent to which the international humanitarian law relied on Islamic sharia. In the second chapter, we explained the duties and the principals of the Red Cross international committee, since it’s responsible for guarding, developing and disseminating the principals of the international humanitarian law. We have concluded that the conceptions of international humanitarian law are well settled in the Islamic sharia as general principals though not adopting the same terminologies. We also found that the ends and principals of the Islamic sharia have sowed the seeds of what is known in the contemporary era, as Humanitarian International law. We can see that in words of the prophet may Allah peace and blessings be upon him, and in the implications of the companions, may Allah bless them, and the views of jurists regarding to the matter of war, the management of Jihad and directing soldiers.